Assessment of two minimally invasive methodologies for sex identification in the European eel, Anguilla anguilla - Michael J. Williamson; Jack A. Brand; Kevin Hopkins; Luke O'Connor; Matthew W. Perkins; Christopher Sergeant; Simon Spiro; Taina Strike; Jessica Whinfield; Rosie S. Williams; Ethan Wrigglesworth; Rosalind M. Wright; et al. (Journal of Fish Biology, 2026)
Sex is an important driver of variation in behaviour, ecology and physiology. Sex identification in the Critically Endangered European eel ( Anguilla anguilla ) currently requires fish sacrifice, or the use of morphological differences such as body length, which can be inaccurate in certain habitats and at intermediate body lengths. Non‐lethal tools for accurate sex identification in this species are therefore required. Here, we test the efficacy of two minimally invasive methods of sex identification: (1) ultrasonography and (2) molecular markers taken from pectoral fin clips. Both methodologies were applied to riverine European silver eel and compared to histological sex identification. Ultrasonography accurately identified the gonads in female eel, with males identified by the absence of detectable gonadal structures. The level of expression of three molecular markers ( dcn, LOC111853410 , kera ) previously used to identify sex in Japanese eel ( Anguilla japonica ) were evaluated. There was no significant differential expression of the three molecular markers between sexes, suggesting that these markers cannot be accurately used to identify sex in European eel. Our findings suggest that minimally invasive imaging using ultrasonography can be a reliable tool for identifying sex in early‐stage adult migratory European eels, with particular use at intermediate sizes (400–500 mm) and animals in habitats where migration potential is limited and may regularly exceed typical growth sizes. This technique can be highly valuable for studies that address ecological, behavioural, conservation and management issues in this Critically Endangered species.

Streamflow regime characterization in the changing boreal ecosystem: wildfire impacts from stream-to-regional scales - Deanna D. Strohm; Christopher J. Sergeant; Josh D. Paul; Jeffrey A. Falke (Science of The Total Environment, 2025)

An interdisciplinary synthesis of floodplain ecosystem dynamics in a rapidly deglaciating watershed - Christopher J. Sergeant; Jonathan W. Moore; Diane C. Whited; Kara J. Pitman; Mark Connor; Erin K. Sexton (Science of The Total Environment, 2024)

Hypoxia vulnerability in the salmon watersheds of Southeast Alaska - Christopher J. Sergeant; J. Ryan Bellmore; Rebecca A. Bellmore; Jeffrey A. Falke; Franz J. Mueter; Peter A.H. Westley (Science of The Total Environment, 2023)

Effects of historic and projected climate change on the range and impacts of an emerging wildlife disease - Stephen J. Price; William T. M. Leung; Christopher J. Owen; Robert Puschendorf; Chris Sergeant; Andrew A. Cunningham; Francois Balloux; Trenton W. J. Garner; Richard A. Nichols (Global Change Biology, 2019)
The global trend of increasing environmental temperatures is often predicted to result in more severe disease epidemics. However, unambiguous evidence that temperature is a driver of epidemics is largely lacking, because it is demanding to demonstrate its role among the complex interactions between hosts, pathogens, and their shared environment. Here, we apply a three‐pronged approach to understand the effects of temperature on ranavirus epidemics in UK common frogs, combining in vitro, in vivo, and field studies. Each approach suggests that higher temperatures drive increasing severity of epidemics. In wild populations, ranavirosis incidents were more frequent and more severe at higher temperatures, and their frequency increased through a period of historic warming in the 1990s. Laboratory experiments using cell culture and whole animal models showed that higher temperature increased ranavirus propagation, disease incidence, and mortality rate. These results, combined with climate projections, predict severe ranavirosis outbreaks will occur over wider areas and an extended season, possibly affecting larval recruitment. Since ranaviruses affect a variety of ectothermic hosts (amphibians, reptiles, and fish), wider ecological damage could occur. Our three complementary lines of evidence present a clear case for direct environmental modulation of these epidemics and suggest management options to protect species from disease.